Implementasi Bimbingan Konseling dalam Mengatasi Kecanduan Gadget Peserta Didik di SMA Santa Rosa De Lima Tondano - Maritje Maria Makalew; Adrianus Dalia (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
This study uses a qualitative approach research method to obtain in-depth and descriptive data regarding the implementation of counseling guidance in overcoming addictiongadget at Santa Rosa de Lima Tondano Catholic High School. In this study, the sources of data for researchers were school principals, teachers, and class X and XI students. Data collection techniques used are observation, interviews, document collection and documentation. The focus of this research is on the three formulations of the problem, namely (1) How is the implementation of counseling guidance to students at Santa Rosa de Lima Tondano Catholic High School? (2) What factors support and hinder the implementation of guidance and counseling? (3) What are the school's efforts in counseling guidance for students who experience addictiongadget?. The results of this study indicate that the implementation of counseling guidance must involve all elements of the school and a support system is needed to achieve successful implementation of counseling guidance. Factors supporting the synergy of school elements, the role of the teacher in providing advice and teaching to students and the relatively small number of students support the effectiveness of the implementation of counseling guidance. The inhibiting factor is the absence of teachers with counseling guidance in schools and students who have not been able to be open about the problems they are experiencing. Researchers found that there had been significant efforts on the part of the school in implementing counseling guidance at Santa Rosa de Lima Tondano Catholic High School, teachers and teaching staff had been able to identify students who experienced addiction.gadget and able to work together with all elements of education in schools in overcoming addiction gadget on students.